Intranasal dexmedetomidine and intravenous ketamine for procedural sedation in a child with alpha-mannosidosis: a magic bullet? - Matteo Trevisan; Sara Romano; Egidio Barbi; Irene Bruno; Flora Maria Murru; Giorgio Cozzi (BMC, 2019)
Abstract Background Procedural sedation is increasingly needed in pediatrics. Although different drugs or drugs association are available, which is the safest and most efficient has yet to be defined, especially in syndromic children with increased sedation-related risk factors. Case report we report the case of a five-year-old child affected by alpha-mannosidosis who required procedural sedation for an MRI scan and a lumbar puncture. We administered intranasal dexmedetomidine (4 μg/kg) 45 min before intravenous cannulation, followed by one bolus of ketamine (1 mg/kg) for each procedure. The patient maintained spontaneous breathing and no desaturation or any complication occurred. Conclusion intranasal dexmedetomidine and intravenous ketamine could be a feasible option for MRI and lumbar puncture in children with alpha-mannosidosis needing sedation.